Carbon nanotechnology : recent developments in chemistry, physics, materials science and device applications - Dai, Liming, 1961- (Elsevier, 2006)
Nanotechnology is no longer a merely social talking point and is beginning to affect the lives of everyone. Carbon nanotechnology as a major shaper of new nanotechnologies has evolved into a truly interdisciplinary field, which encompasses chemistry, physics, biology, medicine, materials science and engineering. This is a field in which a huge amount of literature has been generated within recent years, and the number of publications is still increasing every year. Carbon Nanotechnology aims to provide a timely coverage of the recent development in the field with updated reviews and remarks by world-renowned experts. Intended to be an exposition of cutting-edge research and development rather than a kind of conference proceeding, Carbon Nanotechnology will be very useful not only to experienced scientists and engineers, who wish to broaden their knowledge of the wide-ranging nanotechnology and/or to develop practical devices, but also to graduate and senior undergraduate students who look to make their mark in this field of the future. A comprehensive treatment from materials chemistry and structure-property to practical applications Offers an in-depth analysis of various carbon nanotechnologies from both fundamental and practical perspectives An easily accessible assessment of the materials properties and device performances based on all of the major classes of carbon nanomaterials, including: carbon fiber; diamond; C60; and carbon nanotubes A concise compilation of the practical applications of carbon nanotechnologies from polymer-carbon nanocomposites to sensors, electron emitters, and molecular electronics.
Keywords: Carbon.; Nanostructured materials.; elektronické knihy; electronic books